Effects of early age feed restriction and heat conditioning on heat shock protein 70 expression, resistance to infectious bursal disease, and growth in male broiler chickens subjected to heat stress - Liew, P.K.; Zulkifli, I.; Hair-Bejo, M.; Omar, A.R. (Poultry Science Association, 2003)
The effects of early age feed restriction and heat conditioning on heat shock protein (HSP) 70 expression, antibody production, resistance to infectious bursal disease (IBD), and growth of heat-stressed male broiler chickens were investigated. Chicks were divided into 4 groups: 60% feed restriction on d 4,5, and 6 (FR); exposure to 36 ± 1°C for 1 h from d 1 to 21 (HT); combination of FR and HT (FRHT); and control. From d 35 to 50, heat stress was induced by exposing birds to 38 ± 1°C and 80% RH for 2 h/d. On d 36, each bird was administered 10 times the normal dose of live IBD vaccine. After heat exposure, the FRHT birds had higher HSP 70 density (d 41) and weight gain (from d 35 to 49) and lower bursal histological score (BHS) (d 51) than their HT and control counterparts. The HSP 70 expression and BHS of FR birds were not significantly different from those of the other 3 groups during the heat exposure period. Heat shock protein 70 and BHS data were negatively correlated (r = -0.33, P = 0.0008). We concluded that FRHT could improve weight gain and resistance to IBD in male broiler chickens under heat stress conditions. The improved heat tolerance and disease resistance in FRHT birds could be attributed to better HSP 70 response.